2006
DOI: 10.1590/s1413-35552006000100010
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da rotação do quadril na síndrome da dor femoropatelar

Abstract: Objetivo: A proposta desse trabalho foi investigar o efeito da rotação do quadril na atividade elétrica dos músculos Vasto Medial Oblíquo (VMO), Vasto Lateral Oblíquo (VLO) e Vasto Lateral Longo (VLL) no agachamento a 45º de flexão do joelho associado à posição neutra, rotação lateral a 45º e rotação medial a 15 e 30º de quadril. Materiais e Método: Foram avaliadas 27 mulheres, sendo 15 mulheres normais do grupo Controle (21,1±2,1 anos) e 12 portadoras de Síndrome da Dor Femoropatelar (SDFP) (21,0±2,3 anos). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
(51 reference statements)
0
10
1
2
Order By: Relevance
“…These findings on the squat exercises differ from what is suggested by Gramani-Say et al 21 , that the squat exercise combined with hip adduction should yield greater activation of VM, due to the anatomical position. According to the authors, some fibers of the VM muscle are inserted in the distal portion of the magnus adductor muscle, enhancing the muscle activation of VM when combined with hip adduction.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings on the squat exercises differ from what is suggested by Gramani-Say et al 21 , that the squat exercise combined with hip adduction should yield greater activation of VM, due to the anatomical position. According to the authors, some fibers of the VM muscle are inserted in the distal portion of the magnus adductor muscle, enhancing the muscle activation of VM when combined with hip adduction.…”
Section: Discussioncontrasting
confidence: 99%
“…Along the exercise, the trunk would remain perpendicular to the ground as to avoid mechanical advantage of the hip extensor muscles, which happens with the increase of the spinal flexion angle. 21 The knee flexion at 60° was measured by an acrylic goniometer by Trident ® (Itapuí, São PauloBrazil). At this position, the subject executed the extension of the lower limbs against a fixed bar supported by the shoulders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, caution is recommended during clinical physical therapy practice when performing knee extension MVIC during the last degrees of OKC, when there is greater patellofemoral stress 26 . The VLO muscle requires further studies in people with PFPS given that the present study and other studies 16,27,28 , despite methodological differences, found that this portion does not appear to directly interfere in patellar lateralization and in imbalance. According to our results, these changes are attributed, in principle, to the VLL because there were no differences in the activation of this portion in the PFPS subjects.…”
Section: Discussionmentioning
confidence: 44%
“…For patients diagnosed with PFPS, conservative treatment is always considered as the first and best option. This treatment aims to treat PFPS by means of voluntary exercises aimed at promoting balance between the muscular portions of the femoral quadriceps, especially the vastus medialis lateralis and vastus medialis oblique stabilizers 7 . Among the various manners used in conservative treatment, functional bandaging is a form of treatment used in several pathologies with great effectiveness, correcting the patellar misalignment due to PFPS, through its biomechanical properties.…”
Section: Introductionmentioning
confidence: 99%